Puzzling Politics: A Methodology for Turning World-Systems Analysis Inside-Out - Leslie C. Gates; Mehmet Deniz (Journal of World-Systems Research, 2019)
Can world-systems analysis illuminate politics? Can it help explain why illiberal regimes, outsider parties, and anti-immigrant rhetoric seem to be on the rise? Can it help explain any such nationalchanges that seem destined to shift how nations relate to world markets? Leading surveys of historical sociology seem to say no. We disagree. While there are problems with Wallerstein’s early mode of analyzing politicsin the capitalist world-system from the outside-in, historical sociologists have been too quick to dismiss world-systems analysis. We propose an alternative inside-out approach anchored in a methodology for selecting what to study: those national political transformations which constitute puzzling instances within a given world-historical political process. We recommend promising theoretical lineages to guide empirical research on the selected puzzle: those that specify the elite social bases of politics. We thereby  turn  world-systems  analysis  inside-out.  Our  inside-out  approach  advances  the  project  of  world-systems analysis as a methodology, rather than a theoretical prescription in several ways. First, it addresses an important but largely overlooked question: how to select what to study. Second, it devises a methodology that can, but does not have to, pair with the methodology of incorporated comparisons. Third, it offers a methodology that stimulates, rather than forecloses, theoretical flexibility and fresh interpretations of politics and the world-economy. We illustrate the strengths of this new approach with three books, two of which won the best book award from ASA’s Political Economy of the World System (PEWS) Section.